Terapi Murattal Surat Ar-Rahman Menurunkan Stres Kehamilan - Anni Annisa; Emdat Suprayitno (Fakultas Ilmu Kesehatan, 2019)
Pregnancy is a life process that women will experience after marriage. But not all women have the chance to get pregnant, it is very natural for many women who consider pregnancy to be an extraordinary period so that women focus on filling their pregnancy with activities that make the fetus grow healthy. Spikologis reactions such as stress in pregnant women caused a non-smooth process and the risks experienced by pregnant women, so not all women have a smooth pregnancy. This type of research uses quasy-experiment using one group pre-post test design test. Therapy is measured by the stress level of pregnant women for 15 minutes after Qs therapy. The beneficent. Murattal Audio Qs. Ar-Rahman and the DASS (Depression Anxiety Stress Scales) questionnaire. In this study, researchers used the sample technique in an incidental manner. The sample used as many as 56 pregnant women, consisting of 28 pregnant women who work as career women and 28 people who work as housewives After the Murattal therapy of Qs Ar-Rahman in 56 respondents there was a decrease in the stress level of pregnant women. 35 respondents of pregnant women experienced mild stress with a percentage of 62.5%, with moderate stress as many as 15 pregnant women with a percentage of 26.8%. While for severe stress 6 pregnant women with a percentage of 10.7%.